2009
DOI: 10.1351/pac-con-08-08-28
|View full text |Cite
|
Sign up to set email alerts
|

Dinogunellins A-D: Putative ichthyootoxic phospholipids of northern blenny Stichaeus grigorjewi eggs

Abstract: Dinogunellins A-D, ichthyootoxic phospholipids, have been isolated from the mature eggs of the northern blenny Stichaeus grigorjewi. Their structures were determined based on spectral and chemical methods as a mixture of 2'-or 3'-acylated adenosine 5'-phosphate linked to the α-carboxyl group of L-asparagine through a P-N bond. and named dinogunellins A-D (2-5). Surprisingly, their structures differed from that proposed in the earlier work. This paper describes the isolation and structure determination of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…As actin-polymerization inhibitors, macrolides interfere with cytoskeleton functions, eventually leading to cell death. 242,243 They also inhibit protein synthesis by binding to mitochondrial ribosomes, causing cell arrest, 244 further contributing to their cytotoxicity. No toxicity assays have been made at wholeorganism levels and further analyses are needed to determine the role of these toxins in defense against predation.…”
Section: Phenolicsmentioning
confidence: 99%
See 1 more Smart Citation
“…As actin-polymerization inhibitors, macrolides interfere with cytoskeleton functions, eventually leading to cell death. 242,243 They also inhibit protein synthesis by binding to mitochondrial ribosomes, causing cell arrest, 244 further contributing to their cytotoxicity. No toxicity assays have been made at wholeorganism levels and further analyses are needed to determine the role of these toxins in defense against predation.…”
Section: Phenolicsmentioning
confidence: 99%
“…[270][271][272][273] Since then, dinogunellin was also found in another blenny sh Stichaeus nozawae, and the killish Fundulus heteroclitus (cyprinodontiformes: fundulidae). 274 In a study on the dinogunellin structure of Stichaeus grigorjewi eggs, four forms of the molecule were identi-ed, named dinogunellin-A, B, C, and D. 242 The site of production and mechanism of transfer to the eggs remain unexplored. If ingested, dinogunellin is toxic to mice and guinea pigs, causing illness and death.…”
Section: Phenolicsmentioning
confidence: 99%
“…The distinctive presence of a phosphoramidate P–N bond in dinogunellins is a recurring chemical feature that is widely shared among many nucleotidic antibiotics, e.g., phosmidosines, the antifungal nucleotide antibiotics from Streptomyces durhameusis (see below) [ 270 , 271 ]. In mature eggs of several fish dinogunellins occur as a lipoproteins, complexed with the egg protein vitellogenin [ 272 ]. Interestingly they are absent in immature eggs.…”
Section: Natural Products Containing a P–n Bond (Phosphoramidates)mentioning
confidence: 99%
“…Although not as toxic as tetrodotoxin (TTX), dinogunellin can cause gastrointestinal distress, including nausea, vomiting, abdominal pain and diarrhea. Severe symptoms can even lead to death (Asano & Itoh, 1962;Hashimoto, 1979;Matsunaga, Takahashi, & Fusetani, 2009). Previous reports have indicated that some cases of food poisoning in China and Japan are caused by consumption of roe containing dinogunellin (Asano & Itoh, 1962).…”
Section: Introductionmentioning
confidence: 99%